The relationship between immigrant status, cultural/racial background, and hypothyroidism among middle-aged and older Canadians: An analysis of Canadian Longitudinal Study on Aging dataData are available from the Canadian Longitudinal Study on Aging ( accessed on 28 August 2022) for researchers who meet the criteria for access to de-identified CLSA data. - ZhiDi Deng, PharmD; Karen M Davison, PhD RD; Michelle Cartier, MA; Andie MacNeil, MA MSW; Esme Fuller-Thomson, PhD (Archives of Gerontology and Geriatrics Plus)
Objective: Little is known about hypothyroidism among immigrants. We investigated associations between immigration recency, cultural/racial origin, and hypothyroidism. Methods: Using the Canadian Longitudinal Study on Aging (unweighted n = 26,036), analyses were conducted to examine associations between hypothyroidism and sociodemographic factors including immigrant status, immigrants' cultural/racial origin, and health and dietary intake covariates. Results: The sample included 1,953 individuals with hypothyroidism; most respondents were born in Canada (81.3 %), 55 years+ (60.6 %), with annual household incomes >$50,000 (67.7 %), in a relationship (75.4 %), and had some post-secondary education (62.5 %). Binary logistic regression analyses indicated lower odds of hypothyroidism for those who immigrated to Canada <20 years ago (OR=0.62, 95 % CI 0.42–0.93, p = 0.019) compared to Canadian-born. For South Asian immigrants, the odds of hypothyroidism were 77 % higher than those born in Canada (OR=1.77, 95 % CI 1.18–2.66, p = 0.006). Hypothyroidism was associated with gender, age, marital status, education status, presence of comorbidities, hypertension, drinking behavior, disease risk, bone density, nutritional risk, and dietary intakes of fat, omega-3 fats, fruits and vegetables, pulses and nuts, and calcium containing foods (p's<0.05). Conclusions: We found that immigrants who arrived <20 years ago had significantly lower odds of hypothyroidism, but longer-term immigrants were comparable to those born in Canada. These findings are in keeping with the healthy immigrant effect. The higher odds of hypothyroidism among those from South Asia suggests there may be a need to proactively screen for hypothyroidism in this population. Non-pharmacologic nutrition-based interventions may be helpful in the prevention or management of hypothyroidism, however more research is needed.